2012
DOI: 10.1016/j.celrep.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mitochondrial DNA Segregation in Primate Preimplantation Embryos Precedes Somatic and Germline Bottleneck

Abstract: SUMMARY The timing and mechanisms of mitochondrial DNA (mtDNA) segregation and transmission in mammals are poorly understood. Genetic bottleneck in female germ cells has been proposed as the main phenomenon responsible for rapid intergenerational segregation of heteroplasmic mtDNA. We demonstrate here that mtDNA segregation occurs during primate preimplantation embryogenesis resulting in partitioning of mtDNA variants between daughter blastomeres. A substantial shift toward homoplasmy occurred in fetuses and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 39 publications
8
111
0
3
Order By: Relevance
“…This ES cell shift was suggested to be the result of strong mtDNA bottleneck occurring upon epiblast specification in the few cells directed to somatic lineages. After ES cell stage, mtDNA heteroplasmy levels did not vary considerably between different ES cell clones or in different solid tissues in primates, whereas in oocytes mtDNA segregation appeared to be random in mice and monkeys (25,46). As previously suggested that reprogramming takes iPSC mitochondria back to an epiblast-like stage (31, 49), our results further suggest that also the mtDNA bottleneck is reproduced in vitro during reprogramming.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This ES cell shift was suggested to be the result of strong mtDNA bottleneck occurring upon epiblast specification in the few cells directed to somatic lineages. After ES cell stage, mtDNA heteroplasmy levels did not vary considerably between different ES cell clones or in different solid tissues in primates, whereas in oocytes mtDNA segregation appeared to be random in mice and monkeys (25,46). As previously suggested that reprogramming takes iPSC mitochondria back to an epiblast-like stage (31, 49), our results further suggest that also the mtDNA bottleneck is reproduced in vitro during reprogramming.…”
Section: Discussionsupporting
confidence: 69%
“…However, the exact stage in embryogenesis when this bottleneck occurs has been under debate (25,34,47,48). The biphasic shift in our iPSCs mimics closely the results seen in primate heteroplasmic ES cells, which had shifted toward homoplasmy at early passage (46). This ES cell shift was suggested to be the result of strong mtDNA bottleneck occurring upon epiblast specification in the few cells directed to somatic lineages.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Some fetuses and some stem cell lines derived from the embryos exhibited skewed mtDNA ratios, although there was no evidence of preferential mtDNA selection. This suggested that both variants functioned equally, even though the two mtDNA those of sequences were as different from each other as they were from some other primate species 33 .…”
Section: Studies On Mitochondrial Donationmentioning
confidence: 97%
“…When Lee et al 33 generated macaque oocytes that were heteroplasmic (50:50) for two subspecies mtDNA variants, the resulting embryos underwent marked partitioning of the mtDNA between different blastomeres and to some extent between trophectoderm and inner cell mass (ICM) in the resulting blastocysts. Some fetuses and some stem cell lines derived from the embryos exhibited skewed mtDNA ratios, although there was no evidence of preferential mtDNA selection.…”
Section: Studies On Mitochondrial Donationmentioning
confidence: 99%